Aging-related diseases and autophagy - Çoker Gürkan , Ajda; Palavan Unsal, Narcin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (My University, 2016)
Autophagy is fundamental, evolutionary conserved physiological process at molecular level which targets long-lived cytosolic proteins and organelles to be recycled through lysosomal degradation. Diminished autophagic activity caused cellular stress in many organisms following aging, and inhibition of autophagy in model organisms causes degenerative changes and pathologic diseases observed with high incidence ratio generally in older ages. Consequently the delayed senescence or increased longevity in model organisms often stimulate autophagy, and autophagy inhibition compromises anti-aging effects. The cytoprotective function of autophagy is presented in various human diseases such as lung, liver, cardiovascular diseases, neurodegeneration, myopathies, cancer, stroke, infections and metabolic diseases which are found associated with autophagic targets. These pathologies are defined with their age-dependent characteristics, is not fully understood that how autophagy network regulates metabolism and may cause diseases in age-related manner. In this book chapter, we are going to discuss the autophagy and aging relationship in three different parts. In the first section autophagy and aging relationship is going to be presented through explaining responsible signalling network. The autophagy and age-related neurological disorders, genetic basis of age-dependent diseases and the functional role of autophagy is going to be discussed in the second and third part of the chapter.
Keywords: Autophagy; Aging; Metabolism; Diseases; Sirtuins; AMPKa; Otofaji; Yaşlanma; Metabolizma; Hastalıklar